Usage and Performance of Various Library Software Modules in Engineering Colleges of Karnataka - Mulla, K.R.; Chandrashekara, M.; Talawar, V.G (DESIDOC Journal of Library & Information Technology, 2010)
In India library automation began in the late 1970s in a few special libraries and has now reached most of the university libraries. It has yet to take off in college libraries in Karnataka owing to various problems. Many studies on library automation have been undertaken in the developed countries, but few have been undertaken in India. This study is a survey of engineering college libraries that have omputerised their operations and services in Karnataka. The study is limited to the automated libraries of engineering college libraries in Karnataka. It gives a status on the software packages used by the various libraries, and opinions of the librarians about the performance of the different modules of the software they have used. DOI: 10.14429/djlit.30.387